O conflito entre determinismo e liberdade a partir do problema da consciência no pensamento de Nietzsche : do naturalismo ao expressivismo - Onofri, Wilson Luciano (2024)
The thesis defended here is the possibility of making freedom and determinism compatible in the problem of consciousness based on an expressivist conception of moral agent, in Nietzsche’s philosophy. As an expressivist moral agent, it is understood here that the moral agent is not a previously given entity that needs to be discovered to conduct the action and its evaluation, but first and foremost, the location where transformation processes take place, constituted in the space of tension between the individual and the supra-individual plane where the moral agent is constituted in the social dynamics itself. Thus, the expressivist moral agent would not be behind the action as a causal or intentional entity, but would manifest itself in the action as a totality, in the process of carrying out the action itself. To this end, the development of Nietzsche's thought on the subject was reconstructed based on the tension between naturalism and transcendental philosophy, from the first reflections of youth to maturity, identifying a solution to the problem in expressivism. Furthermore, it was necessary to identify the notion of freedom desired by Nietzsche in the idea of self-awareness, and not just linked to the mere idea of consciousness, and thus relate the contemporary problem of philosophy of mind with Nietzsche's program of self-creation